Translational progress and bottlenecks in neurotransmitter-cancer research [2000–2025]: an integrated bibliometric and interventional trial analysis - Zhang, Ming; Sun, Weihao; Ma, Yizhao; Zheng, Jialin C.; Wu, Qihui; Gao, Ge (Translational Cancer Research, 2026)
Neurotransmitter signaling influences cancer initiation, progression, and therapy response. We systematically characterized the field’s intellectual structure, thematic evolution, and translational trajectory.